ANALISIS PERLINDUNGAN KONSUMEN TERHADAP ANAK YANG MENGKONSUMSI JAJANAN MENGGUNAKAN BAHAN BERBAHAYA DI PEKANBARU - Mifta, Sarah; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Human is a consumer, there is no difference between the consumer of the child with the adult consumer, cheating on the consumer of Ana more susceptible to occur, conducted by the child Hawker vendors in the school, the child's absence becomes Pratik in Perpetrators of business fraud to gain maximum profit. Children can not tell which snacks are good for consumption and which is not good. Sometimes children who are consumers rarely pay attention to the food they buy on food vendors in schools and outside schools. The adverse effect of indirect harmful material will be felt directly by a child or an adult, its influence will be seen in the long run. Food is all that comes from sources of biological and water, whether processed or untreated, which is intended as food and beverage for humans, including food additives, food ingredients, and other ingredients used in preparation, processing and/or manufacture of food and beverage. School kids snacks are foods that are sold around schools and many school children consume. The goal is to know the protection of the child to the food actors who use hazardous materials as well as the responsibility of business actors for losses suffered by the child consuming.This type of research research can be classified, sociological, because in this research the author directly conduct research on the location or place in a thorough to provide a complete and clear picture of the problems studied, This research was conducted at elementary school which is in Pekanbaru and the Great Hall of Medicine and food, while population and samples are parties related to the issues investigated in this study, seumber data used primary data, data Data collection techniques in this study with interviews and literature studies. "The results of the study that in school children's snacks are still traders who are cheating and wearing hazardous materials in the food they sell. Business actors still do not know the responsibility for the losses suffered by consumers. The Government in this case is represented by Bbpom has sought to provide protection to the has of children.Keywords: snacks, hazardous materials, children.